Cyberloafing Behaviour On Employee Performance at PT. Telkomsel Serang Branch - Gracia, Bunga Astra; Kusniawatid, Nia (Adpebi Science Series, 2022)
This research aims to determine the effect of organizational commitment and cyberloafing behavior on employee performance at PT. Telkomsel Serang Branch. The method used is a quantitative approach to comparative causal. By using the census sampling method, the sample dan population for this research, totaling 88 persons, were all employees at PT. Telkomsel Serang Branch. The data analysis in this research used multiple regression analysis obtained through a validity test, reliability test, and classical assumption test so that it can test the hypothesis by using the SPSS 23.0 program. The results of this study indicate that (1) There is a significant effect of organizational commitment (X1) on employee performance (Y) at PT Telkomsel Serang Branch With the correlation value of 0.248 means that the variable of organizational commitment has a low level of relationship with the coefficient of determination is 6.2%. (2) There is a significant effect of cyberloafing behavior (X2) on employee performance (Y) at PT Telkomsel Serang Branch, with a correlation value of 0.332 means the variable of cyberloafing behavior has a low level of relationship with a coefficient of determination of 11%. (3) There is a simultaneous significant effect between organizational commitment (X1) cyberloafing (X2) and employee performance (Y) at PT Telkomsel Serang Branch with a correlation value of 0.390 means that both variables have a correlation level with a coefficient of determination of 20.9%. Hypothesis testing obtained F count (11.203)> Ftable (3.10)